Court of Justice on Reformation Flows - Larusmee, Somphum; Phosing, Assoc.Prof.Dr.Phakdee (Journal for Developing the Social and Community, 2018)
The past political conflicts have had a direct impact on the socio-economic system and the state administration, calling for a reform of the country in every dimension. It is the origin of the Constitution of the Kingdom of Thailand 2017. The reform of the country 11 aspects, including the judicial process. And the action must be consistent with the national strategy. The reform of the country's justice system has set the issue of 10 reforms. And the proposal to have or amend the law to support the implementation of individual issues clears. The judiciary is a judicial organization that sets the strategy and action plan in line with the reform of the justice system. It focuses on access to reduce the disparity, bringing justice to the people to achieve the goals of the national strategy.